The lost lizards of Christmas Island: A retrospective assessment of factors driving the collapse of a native reptile community. Issue 2 (13th January 2021) - Emery, Jon‐Paul; Mitchell, Nicola J.; Cogger, Harold; Agius, Jessica; Andrew, Paul; Arnall, Sophie; Detto, Tanya; Driscoll, Don A.; Flakus, Samantha; Green, Peter; Harlow, Peter; McFadden, Michael; et al.
Abstract: Until recently, the reptile fauna of Christmas Island in the Indian Ocean comprised five endemic species (two skinks, two geckos, and one snake) and one native, non‐endemic skink. Four of these species were common and widespread until at least 1979, but by 2012 had disappeared from the wild. During the years of decline, little research was undertaken to examine why the species were disappearing. Here, we use a retrospective expert elicitation to rank potential factors that contributed to the loss of Christmas Island's reptiles and to assess the likelihood of re‐establishing populations of two species now listed as Extinct in the Wild. We additionally considered why one endemic lizard, the Christmas Island giant gecko ( Cyrtodactylus sadleiri), and three introduced lizards remain common. Experts considered that the introduced common wolf snake ( Lycodon capucinus ) was the most likely cause of decline, as its temporal and spatial spread across the island closely matched patterns of lizard disappearances. An Asian co‐occurrence in recent evolutionary timeframes of the common wolf snake with the Christmas Island giant gecko and three introduced reptiles was the most marked point of difference between the extant and lost lizard species. The demise in less than 20 years of 80% of Christmas Island's native lizard assemblage highlights the vulnerability of island fauna to invading species.